Evaluate the Effect of Education Interventions in the Prevention of Diabetic Foot Ulcers through Knowledge of the Disease and Self-Care Practices in Saudi Arabia - Ahmed, Nagwa Mohammad; Khresheh, Reham Mohammad (Archives of Clinical and Medical Case Reports, 2018)
Background: Diabetes mellitus places a substantial burden on society worldwide. Diabetic foot ulcers are a challenging problem for clinicians. Seven generally accepted detriments to healing of diabetic foot ulcers were identified: infection, glycaemic control, vascular supply, smoking, nutrition and deformity. Aim: To evaluate the effect of education interventions in the prevention of diabetic foot ulcers through knowledge of the disease and self-care practices. Methods and design: A quasi-experimental, design used. The study conducted in the Internal Medicine Department and Outpatient clinic at Umulj general hospital -2016. The study sample consists of 60 adult patients with diabetes mellitus. Approval to conduct the study obtained from the Ministry of Health and the University of Tabuk Research Ethics Committee. Results: This study shows that, a significant relationship between levels of patient's knowledge, practice and level of education. The result of the present study concluded that implementation of the developed educational program showed significant improvement in the patients level of knowledge, patients ability to perform self-foot care and level of patient awareness after program implementation.